Inter-Professional Collaboration in Prevention and Management Problems of Infant and Toddler Nutrition - Retno Asti Werdhani (Faculty of Medicine, Public Health, and Nursing, 2020)
One of the functions of the primary care/family physician in case management is as a care coordinator/coordinator of the patient’s management1. McDonald defines a care coordinator as a patient’s management activity in healthcare that involves two or more participants (including patients) to improve the quality of health services. The definition emphasizes the need for collaboration between doctors and various parties including patients, families, and other health workers in managing health problems2. This paper emphasizes coordination and collaboration between health workers and families, which aims to increase knowledge and perceptions of families and communities to prevent malnutrition events such as failure to thrive, or obesity in children in the management of the first 1000 days of life.Management of the first 1000 days of life and growth and development monitoring needs doctors who motivate as well as parenting guidance to be able for caring and feeding the baby, as well as directly monitor the growth and development of their children. Many perceptions and stigmas develop in community can affect parenting parents towards their children. Accordingly, the function of the family physician is expected to have the ability as a care coordinator to support the successful management of the first 1000 days of life. This service requires collaboration between doctors and other healthcare professionals. This is in line with a spirit of partnership and cross-sector cooperation3. Primary care/family physician responsible for providing health services sustainably and comprehensively to individuals, families, and the community, in collaboration with other health workers. Primary care/family physicians manage various resources for the benefit of patients and families. Health services in primary care services provide primary to tertiary prevention services4, which doctors cannot do alone. Primary care/family physician is not only responsible for primary prevention and screening, however, must also be prepared to manage health problems in the first 1000 days of life, growth, and development, including facilitating referral and reconciliation. This responsibility proves the importance of collaboration practice in primary care services.